HERMENEUTICAL KEYS (Sebuah Metode Alternatif dalam Studi al-Quran Perspektif Farid Esack) - Luqman Abdul Jabbar (Khatulistiwa, 2013)
"Theology does not merely mean dealing with the "affairs of "God: hell, heaven and so forth. To Esack, theology that is focuses too much on God --while God does not need to be taken care of-- is redundant and consumes too much unnecessary energy. Esack believes that theology should be made simple, instead of being gripped tightly for the purpose of individual piety "(quoted from “Interview with Farid Esack" on http//www.tempo.co.id).